Strengthening Digital Law Enforcement Strategies Through Integrated Cyber Policing Systems - Rubiyo, Rubiyo (Journal of Creativity Student, 2025)
The rapid growth of cybercrime has placed significant pressure on law enforcement agencies to adopt specialized technologies and investigative frameworks known as cyber policing. This study examines the operational effectiveness, technological requirements, and institutional challenges of implementing integrated cyber policing systems. A mixed-methods approach was applied, combining quantitative analysis of cybercrime reports between 2019 and 2023 with qualitative interviews involving 38 cyber investigators, digital forensic analysts, and incident response personnel. Results indicate that after the adoption of advanced cyber policing tools—including automated threat analysis, digital triage systems, and cross-platform data integration—case-handling time improved by 33%, and digital evidence retrieval accuracy increased from 61% to 86%. Investigators also reported better interdepartmental collaboration and improved situational awareness regarding threat landscapes. However, the study identifies major barriers, including disparities in forensic equipment, limited legal instruments for cross-border data access, and insufficient training for emerging technologies such as AI-assisted investigations. The findings contribute to policing science by presenting an analytical model of cyber policing capabilities and outlining key governance, technical, and operational recommendations necessary for building effective and resilient digital law enforcement systems.